Development of multi-robot system : coordination and formation - Wong, Guan Xiong. (2009)
This report outlined the project on coordination and formation of a multi-robot system. Nowadays, robots are contributing greatly to the society. However, having just one robot to do a task will not be as efficient as multiple robots doing the same tasks. The project involved developing multiple robots that would maneuver in a formation due to the environment or space constrain.